Love’s Imperfection - Cheryl Mattingly (Suomen Antropologi, 2014)
This paper concerns friendship as an aspect of family love and its fragilities. I explore love as an on-going ethical demand and problem in family life, one that can present continual obstacles to the ability to continue as a family. I also look at intra-family friendship as a means for addressing such threats. Drawing upon long-term fieldwork among African American families caring for children with chronic illnesses and disabilities (Mattingly 2010a), I explore a situation faced by one of these families when a household accident badly injures one of the children. Although I examine a family rupture, I part company with the widely held view in anthropology that the properly moral (or ethical) needs to be radically contrasted with the ordinary. Rather, I argue that the ordinary can  provide resources for what Stanley Cavell calls ‘moral transcendence’.